Bentuk Perancangan Model Dan Pola Ilmu Komunikasi Hindu Berbasis Budaya Nusantara - Untung Suhardi; I Wayan Budha; Wayan Tantre Awiyane; Nyoman Sujawan; Bhisma Adinatha; I Made Rahayu Kardikayasa (Jayapangus Press, 2023)
The communication is part that cannot be separated by the life of human beings especially in the interaction, in this also happened in relation to form of communication which is in counseling Hinduism running. In this research problem basic design is a model and patterns of communication based nusantara Hindu culture. The purpose of this research is to analyze model on the design and the communication of Hindus in Jakarta. Methods used is qualitative analysis by approach phenomenology constructivism and the type of data using interview. Research findings that is the kind of design model and the pattern the science of communication hindu based nusantara consisting of; synergy institutions, moderation and development, the media and dialectics communication, and harmony and culture was also become urgen must be considered because of continued think between a man and cultural goes to ground a extension workers.This, can be delivered that there is a guidance that sustainable done with understanding from their mastery of the material, information media and the adjustment of with local knowledge in effect in the region local.